"I wouldn't have hit you, but you would have killed your baby:" exploring midwives' perspectives on disrespect and abusive Care in Ghana - Veronica Millicent Dzomeku; Adwoa Bemah Boamah Mensah; Emmanuel Kweku Nakua; Pascal Agbadi; Jody R. Lori; Peter Donkor (BMC, 2020)
Abstract Background Quality maternal health reduces maternal and neonatal mortality and morbidity. Healthcare professionals, including midwives, are significant agents for the promotion of quality maternal health. Frequents reports of disrespect and abuse of childbearing women by midwives during intrapartum care are becoming common, suggesting that many of these agents are engaging in care practices that compromise quality maternal health. Thus, understanding midwives' descriptions and experiences of the phenomenon is critical to addressing the threat. This paper, therefore, explored the understanding of midwives on D&AC and their occurrence in professional practice in a tertiary health facility in Kumasi, Ghana. Methods An exploratory descriptive qualitative research design using an interpretative approach was employed in the study. Data were generated through individual in-depth interviews. Data saturation was reached with fifteen interviews. The interviews were audio-recorded and transcribed verbatim. Open Code 4.03 was used to manage and analyse the data. Results The midwives understood D&AC. They also confirmed meting out or witnessing colleagues engage in D&AC in their professional practice. The midwives described D&AC as the provision of inadequate care and the overlooking of patient-centred care, and verbal, physical, and psychological abuse. The themes revealed that socio-economic inequalities, provider perception and victim-blaming, and health system-related factors facilitate D&AC. It emerged that the following marginalized groups were at high risk for D&AC: the non-compliant, mentally ill, HIV/AIDs+, teenagers, poor, and childbearing women on admission at the general labour ward. Conclusion The midwives understood D&AC and revealed that it frequently occurred in their professional practice. Frequent in-service training on respectful maternity care and monitoring of care provision in healthcare facilities are needed to eliminate the incidence of D&AC.